Asesmen Portofolio dan Penggunaan Kids Doodle untuk Meningkatkan Perkembangan Mewarnai Anak Usia 4-5 Tahun: The Portfolio Assessment and Use of the Kids Doodle App to Improve Coloring Development in 4-5 Year Old Children - Luluk Asmawati; Humaidah; Alifa Azzahra; Devita Aurazahra; Juita; Gita Mayasari; Nabila Nasywa Hanifah (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
This study aims to analyze the role of digital-based portfolio assessment in supporting the artistic development of children aged 4–5 years through the use of the Kids Doodle application, as well as to identify the ease of use of the Kids Doodle application in Early Childhood Education (PAUD) learning. This study uses a qualitative approach with a library research method. Data sources were obtained from accredited national journal articles, reference books, and scientific documents relevant to portfolio assessment, early childhood artistic development, and the use of digital media in ECE learning. The research subjects did not directly involve children but focused on relevant previous research results. Data collection techniques were carried out through documentation, while data analysis techniques used content analysis through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the use of the Kids Doodle application contributes positively to the artistic development of early childhood, particularly in enhancing visual creativity, expressive abilities, and fine motor coordination through digital coloring activities. Other findings indicate that the Kids Doodle application is very easy to use due to its simple interface, child-friendly features, and attractive color and brush options. The integration of portfolio assessment allows educators to document children's artistic development authentically and continuously. Thus, the use of the Kids Doodle application combined with portfolio assessment can be an innovative alternative to art learning media that is in line with the developmental characteristics of early childhood.   ABSTRAK  Latar belakang penelitian yaitu teknologi pendidikan bidang anak usia dini memerlukan fasilitasi pembelajaran dan asesmen digital untuk meningkatkan keterampilan belajar abad 21 anak usia dini. Penelitian ini bertujuan menganalisis asesmen portofolio dan penggunaan kids doodle untuk meningkatkan perkembangan mewarnai anak usia 4-5. Inovasi teknologi pembelajaran menggunakan kids doodle memfasilitasi kegiatan mewarnai dan asesmen portofolio digital anak usia dini. Subjek penelitian berjumlah 10 anak di TK Amanah Kota Serang. Metode penelitian menggunakan kualitatif naturalistik. Teknik pengumpulan data menggunakan observasi, dokumentasi portofolio. Teknik analisis data menggunakan analisis konten. Temuan-temuan hasil penelitian: (1) asesmen portofolio bahwa 10 anak mampu menyimpan karya digital dengan berkembang sangat baik pada aspek perkembangan mewarnai, kelengkapan hasil karya, kerapihan, dan keaslian karya; (2) penggunaan kids doodle berkembang sangat baik bahwa 10 anak mampu menggunakan kids doodle pada aspek kemudahan, keterlibatan, pemilihan objek gambar, dan menyimpan karya; (3) perkembangan mewarnai berkembang sangat baik bahwa rata-rata 10 anak mampu mewarnai dengan aspek komposisi warna, pemilihan krayon digital, kesesuaian tema, dan kreativitas. Dampak penelitian yaitu asesmen portofolio digital dan penggunaan kids doodle dapat meningkatkan perkembangan mewarnai anak usia 4-5 tahun berkembang sangat baik.